PRE-TESTING ASSESSMENT OF REASONING ABILITY TO THE COLLEGE STUDENTS (Case Study in IKIP Bojonegoro East Java) - Netti Yuniarti; Fatma Fatma; Sri Kusnita (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
In relation of the reasoning process, language structure actually reflects the structure of the mind itself. Language are tightly related to the thinking and reasoning. This process are proceeds from the observation of the senses or the empirical observation in the mind which then produces a number of propositions. As an thinking activity to draws a conclusion, it is necessary to do an evaluation in the form of evaluative question to measure one's reasoning ability in order to achieve effective and objectives results. The research purposes were determined a valid question that can be used to measure reasoning abilities in according with indicators and reasoning dimensions. This research is quantitative research with data analysis techniques used R point Biserial and KR-20. Based on the experiments of 46 items, the r-pbi value of each drop question is (1) 0.120, (2) 0.444, (3) 0.443, (4) 0.263, (5) 0.341, (6) 0.014, (7) 0.011 and (8) 0.382. The value of KR-20 is 0.531 with an average value of pi 0.323, qi 0.677, k 38, totally var of 14.83, and p*q 0.219, Σ p*q 7.159. Thus to test the reasoning ability on the students were obtained the number of valid items as the final instrument is 38 items of 46 items that have been tested first.